2019
DOI: 10.1111/jpn.13156
|View full text |Cite
|
Sign up to set email alerts
|

Organic trace minerals on productive performance, egg quality and immune response in Bovans White laying hens

Abstract: This study was performed in 360 laying Bovans White hens and aimed to evaluate the effect of Carbo‐Amino‐Phosphate‐Chelates (CAFQ) as a mineral premix and its 30% reduction by compared to inorganic trace minerals (ITM) concerning its performance, egg quality, tibia breaking strength and immunity. Sixty‐week‐old hens were assigned into three treatments with 10 replicates of 12 birds each. Treatments were as follows: (a) (100% ITM), (b) (100% CAFQ) and (c) (70% CAFQ). Based on the results obtained during 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Trace elements, as coenzyme factors of many metal enzymes, play important roles in digestion, absorption, metabolism, immune response, and biosynthesis ( 1 , 2 ). To meet the requirement of animals, inorganic trace elements were commonly supplemented in diets.…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements, as coenzyme factors of many metal enzymes, play important roles in digestion, absorption, metabolism, immune response, and biosynthesis ( 1 , 2 ). To meet the requirement of animals, inorganic trace elements were commonly supplemented in diets.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the study of Gheisari et al [ 31 ], feed intake and feed conversion ratio were significantly affected by forms and dosage of Mn, Zn, and Cu. Ramos-Vidales et al [ 17 ] reported that the treatments of organic trace elements (Carbo-Amino-Phosphate-Chelates) had no significant effect on the ratio of feed to egg, egg yield, and egg weight production performance of laying hens. The reasons for the difference may attributed to composition of basal diet, the concentration and sources of trace elements, interaction between minerals, and daily management of layers [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that organic trace elements improved laying performance, increased mineral absorption, increased the mineral concentrations of tissue, and decreased mineral excretion compared to inorganic trace elements. Different concentrations of supplemental trace elements also can affect the above-mentioned parameters [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic trace elements in the chelated forms have several advantages: they are stable in the gastrointestinal tract and are protected from the formation of complexes with other food components that inhibit their absorption (Vieira, 2008). Also, the addition of minerals in the chelated form improves their transport and absorption in the birds' intestines (Ramos-Vidales, 2019). Despite the high level of bioavailability in comparison with non-organic trace elements, their chelated forms are much more expensive, therefore it is not economically feasible to replace them by 100% in the diet of chickens on small farms.…”
Section: Introductionmentioning
confidence: 99%